STRATEGY OPTIMAL PROFIT COMPANY ACHIEVEMENTS IN ENERGY SECTOR (CASE: PT XYZ) - Dwi Widodo Primantoro; muhammad Firdaus; Bunasor Sanim (Value : Jurnal Manajemen dan Akuntansi, 2020)
Abstract XYZ is an oil company active in the exploration, processing and sale of oil products and gas in Indonesia. The company currently requiresstrategy that would encourage businesses to be better. The method used in this research is SWOT and QSPM, while the data used are primary and secondary data. The results of this study showed that XYZ company offered five alternative strategies that are expected to drive corporate performance becomes better, among others, 1) Improving the resulting still large exploration potential of existing resources. 2) Develop the LNG business as a manufacturer. 3) Improving the competitiveness of the processing business. 4) Conducting investigations in order to support the realization of the theme of "aggressive upstream, midstream and downstream profitable" 5) Doing continus improvement in the management process. Keywords :Strategy, SWOT, QSPM